A cardiac and subcutaneous canine dirofilariosis outbreak in a kennel in central France - Laidoudi Younes; Ringot David; Watier-Grillot Stéphanie; Davoust Bernard; Mediannikov Oleg (Parasite, 2019)
Canine dirofilarioses are nematode infections caused by two species of the genus Dirofilaria: D. immitis and D. repens. We describe here an outbreak of D. immitis and D. repens infection in military working dogs (MWDs) housed in a kennel in the Indre department (centre of France). Out of a total of 17 dogs, 6 (35.2%) tested positive for D. immitis, D. repens or both parasites. Infested dogs were treated and prophylactic measures were implemented for the entire kennel staff. To our knowledge, this is the first documented description of an outbreak of canine cardiopulmonary dirofilariasis in the center of France, unlike in the south of this country, where D. immitis and D. repens dirofilariasis are enzootic. In France, as mosquito vectors expand their territory and new non-native vectors are introduced, it is likely that the distribution area of these two diseases of domestic and wild carnivores will be wider and underestimated.